Clustering analyses in peptidomics revealed that peptide profiles of infant formulae are descriptive. Issue 1 (30th December 2014) - Lambers, Tim T.; Gloerich, Jolein; van Hoffen, Els; Alkema, Wynand; Hondmann, Dirk H.; van Tol, Eric A.F.
Abstract Prompted by the accumulating evidence on bioactive moieties of milk‐derived peptides, novel methods were applied to compare the peptide composition among commercially available hydrolysate formulations and to determine batch‐to‐batch variations of protein hydrolysate products. Despite the availability of general methods to measure, for example, the degree of hydrolysis and peptide mass distribution at a high level, the objective of this study was to more qualitatively compare peptide sequences and composition. By a comprehensive approach combining peptidomics technologies and multivariate clustering analyses, the peptide profiles of different hydrolyzed milk protein formulations were compared. Moreover, peptide profiles of various hydrolysate batches that had been produced over a period of 5 years were included. Coupling of identified peptide sequences to the position in their corresponding milk proteins produced numerical datasets that subsequently were utilized for multivariate data analyses. These analyses revealed that batch‐to‐batch variation in the peptide profiles of a specific extensively hydrolyzed casein preparation was low. Moreover, extensive multivariate evaluations revealed that the peptide profiles of different commercially available hydrolyzed milk protein formulations provided a descriptive and distinct signature. Overall, the described methodology may contribute to the field of peptide research as observed dissimilarities in peptide profiles of similar products may be related to differences in their overall functionality.